Independent learning of English literature students: learning from an Iranian experience - Kashefian-Naeeini, Sara; Ramlee Mustapha, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Independent learning is imperative for it can facilitate significant and faster development of a nation’s human resource. Over the last two decades, more active roles are given to language learners and independent learning is taking momentum in the area of language learning. This study sought to investigate independent learning among university students of the Shiraz University majoring in English Literature at the department of Foreign Languages and Linguistics. Analysis of variance and t-test for independent samples were conducted to compare independent learning among students with different learning backgrounds. It was found that professional status influenced students’ independent learning in favour of those students who had an occupation. However, other learner variables did not have such an impact on students’ independent learning. This finding might be instructive for Malaysia’s institutions specializing in English and other foreign languages.